Succinic Acid Recovery from a Glycerol-Based Solution Using Phosphonium Ionic Liquids Supported by Cosmo-Rs - Quijada-Maldonado, E; Olea-Chandia, F (Elsevier B.V., 2022)
Succinic acid has been considered a promising chemical building block that can be bio-produced using renewable resources. However, one of the biggest challenges in the bioproduction of this acid is the extraction and purification process. Currently, to extract and improve the purity of the produced succinic acid, a liquid-liquid extraction using organic solvents and extractants is performed. In this work, a liquid-liquid extraction of succinic acid from a model fermentation solution of Yarrowia lipolytica yeast broth (succinic acid + glycerol + water) is studied. The liquid-liquid extraction was carried out using hydrophobic phosphonium-based ionic liquids as extractants, for a 1:1 phase-volume ratio during 24 h at two different temperatures (298.15 K and 310.15 K) measuring the differences in the concentration of succinic acid and glycerol in the aqueous feed phase after 24 h to quantify the extraction percentage and, the succinic acid / glycerol selectivity. To obtain the succinic acid /water selectivity, the water concentration in the IL phase was calculated using Karl Fischer titration. With an extraction percentage of 78.4% for succinic acid and, a selectivity of 103 and 157 respectively for succinic acid /water and succinic acid /glycerol at 310.15 K, the best studied ionic liquid was [P6,6,6,14][PHOS] being 10 times higher than octanol, which is commonly used as a comparative conventional solvent. On the other hand, a molecular simulation of liquid-liquid extraction generated in COSMO-RS, allowed to validate the experimental results, also indicating that the strong hydrogen bond interactions of [P6,6,6,14][PHOS] and succinic acid were responsible for the excellent values obtained. Finally, the dissolved succinic acid in the organic phase was easily removed with an ultra-pure water striping using liquid-liquid extraction at 298.15 K for 40 min with a 1:1 phase-volume ratio. © 2022 Elsevier B.V.